Homoleptic borates and aluminates containing the difluorophosphato ligand – [M(O2PF2)x]y− – synthesis and characterization. Issue 15 (18th March 2015) - Schulz, Christoph; Eiden, Philipp; Klose, Petra; Ermantraut, Andreas; Schmidt, Michael; Garsuch, Arnd; Krossing, Ingo
Abstract : A new class of WCAs…? The difluoro-phosphato ligand (O2 PF2 ) was used for the synthesis of borates and aluminates of the [M(O2 PF2 ) x ] y − -type in order to generate weakly coordinating anions. Abstract : Weakly coordinating anions (WCAs) with the difluorophosphato ligand (O2 PF2 ) were the target of this study. Initial experiments were conducted towards the preparation of homoleptic aluminates of the well-studied [Al(OR)4 ] − -type. The preparation of the initial target structure Li[Al(O2 PF2 )4 ] failed due to the remaining Lewis acidic character of the central aluminum atom. Instead, the formation of Li3 [Al(O2 PF2 )6 ] and Al(O2 PF2 )3 was observed with hexacoordinate aluminum atoms and verified by NMR, IR and X-ray crystallography. A possible mechanism towards these compounds was postulated in the solvent induced dismutation of the tetracoordinate Li[Al(O2 PF2 )4 ]. A singly charged WCA was realized by the exchange of the central aluminum atom for boron. The [B(O2 PF2 )4 ] − anion was prepared starting from BH3 ·S(CH3 )2 and boron tribromide leading to the protic room temperature Ionic Liquid (IL) [H(S(CH3 )2 )][B(O2 PF2 )4 ] and the neat liquid Brønsted acid H[B(O2 PF2 )4 ], respectively, representing a significantly improved synthesis with regard to the first experiments of Dove et al. The basicity of the [B(O2 PF2 )4 ] − anion and its WCA quality were investigated on the basis of the IR-spectroscopic NH-scale and the salt [H(N(Oct)3 )][B(O2 PF2 )4 ] that places it better than all oxyanions and close to the carboranate based WCAs. A pathway to the solvent free pure Li[B(O2 PF2 )4 ] salt was established on a multi-gram scale with excellent purities enabling electrochemical applications (verified by NMR, IR, X-ray crystallography and cyclovoltammetry).